Sexualidade das mulheres envelhescentes: a idade de grandes transformações e desafios - Rolim, Carolina Morais Miranda (2013)
The average life expectancy of women in 2008 reaches 76.6 years of life and men 69.0 years of life. The reduced levels of fertility and mortality in Brazil has made changes in the age pattern of the population. Two conditions are contributing to the increasing number of elderly and configuration of a new demographic reality they are: the reduction of mortality rates and declining fertility rate. The main diseases that can affect the sexuality of older women are the ones who commit the genitals or pelvic surgeries plus some. Indirectly, by general weakness, anxiety, depression and pain, certain chronic diseases may affect the attainment of pleasure. The objectives of this study were to explore the experiences of women during the menopause / perimenopause; identify women's perceptions about aging; see how women experience the menopause phase / climacteric, check changes in sexuality of aging. This research was developed in the qualitative paradigm, and for the recruitment of subjects in this study, we used the methodological technique "Snowball" well known as snowball, with a total of ten envelhescentes women, aged between 50 and 59 years. Data were collected through semi-structured interviews. Were performed transcription, transcription and textualization of all narratives. In data processing, we used the Content Analysis Bardin. The data analysis resulted in the development of three descriptive categories, which reveal the experiences of women during the menopause / perimenopause. The results show that aging is seen as something natural, a physiological process in the life of all people. For some women, aging is seen as an acceptable event because there is no way to avoid it. Menopause is seen by many women as a defining event in their lives. For some this phase represents a negative event, a real pain. Some women started to not feel desired by their partner, because they believe that their body is not what it was before. This study enabled us to identify the experiences of women during the menopause / perimenopause. In relation to sexuality many women reported significant changes over time. Ceased to feel desired by their partner and noticed decreased libido, reducing the frequency of sex or even sexual practices for partner satisfaction. Some women also reported discomfort during intercourse due to vaginal dryness own this phase. These changes in sexual life led some women to seek other forms of care and affection, rather than the act itself. There was a shortage in relation to publication of scientific papers on the subject under study